Developing Information Technology Law and Legislation: Analysis of International Experience and Possibilities of Its Application in Ukraine - Aristova, Irina; Brusakova, Oksana; Koshikov, Denis; Kaplya, Oleksandr (Universidad Hemisferios, 2021)
The purpose of this article is focusing attention on the relevant problematic issues that exist in the sphere of legal regulation of domestic area of high technologies, as well as finding ways of their effective solution. Noted that the legal regulation of objects and phenomena surrounding the domestic information technology (IT) sphere is quite weak and insufficient compared to other countries. Effectively functioning practices of legal regulation of the sphere of high technologies that exist in developed democracies are analyzed for their compliance with the realities of the domestic legal system. Considerable attention is paid to the characteristics of the current state of functioning of IT law and legislation in democracies. The initial successes that have already been achieved in Ukraine in relation to the IT sphere in the past were analyzed. The perspective directions of further development of IT law, as well as related domestic and international legislation, are considered. It is pointed out that the development of both the domestic high-tech industry and the functioning of IT law and legislation are inextricably linked with the democratization of the country. The methodological basis for writing the article was a set of general scientific and special methods and techniques of scientific knowledge.